2021
DOI: 10.3389/fneur.2021.707723
|View full text |Cite
|
Sign up to set email alerts
|

Different Catechol-O-Methyl Transferase Inhibitors in Parkinson's Disease: A Bayesian Network Meta-Analysis

Abstract: Parkinson's disease (PD) is a common, chronic, progressive, debilitating neurodegenerative disease. The current levodopa treatment requires the addition of other drugs, such as catechol-O-methyl transferase (COMT) inhibitors, to alleviate motor fluctuations in advanced PD. Therefore, a theoretical reference for treatment is urgently needed. In this study, an appropriate search strategy was used to screen eligible studies on different drugs to treat patients with PD from the Embase, PubMed, and Cochrane Library… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…However, tolcapone has safety concerns owing to fulminant hepatotoxicity [ 31, 32 ]; thus, entacapone is currently more widely used than tolcapone in patients with advanced PD [ 33 ]. Another recent network meta-analysis showed that opicapone and entacapone were slightly inferior to tolcapone in on-time increase; however, the main outcomes of the present study, including off-time reduction and on-time increase without troublesome dyskinesia, were not analyzed [ 34 ]. According to the BIPARK-I trial, the reduction in off-time was higher in the opicapone 50 mg group (–116.8 min) than in the entacapone 200 mg group (–96.3 min) [ 8 ].…”
Section: Discussionmentioning
confidence: 94%
“…However, tolcapone has safety concerns owing to fulminant hepatotoxicity [ 31, 32 ]; thus, entacapone is currently more widely used than tolcapone in patients with advanced PD [ 33 ]. Another recent network meta-analysis showed that opicapone and entacapone were slightly inferior to tolcapone in on-time increase; however, the main outcomes of the present study, including off-time reduction and on-time increase without troublesome dyskinesia, were not analyzed [ 34 ]. According to the BIPARK-I trial, the reduction in off-time was higher in the opicapone 50 mg group (–116.8 min) than in the entacapone 200 mg group (–96.3 min) [ 8 ].…”
Section: Discussionmentioning
confidence: 94%
“…Chronic use of L-DOPA leads to certain non-motor symptoms, like L-DOPA-induced-dyskinesia (LID), motor fluctuations, including early-morning off (lack of the efficiency of drug after wake up), wearing-off (reduction of duration of action), delayed-on (delay of drug action), no-on (dose-failure, lack of effect after drug dosage), and on-off phenomena (ON-time, in which the symptoms are under control and the patient can move without difficulty versus the sudden appearance of OFF-time, when the patient is immobile). The mechanism for this is still unclear [2][3][4][5][6].…”
Section: L-dopamentioning
confidence: 99%
“…Opicapone combines several advantages: Its potency is similar to that of tolcapone, 6 it only needs to be taken once daily and it provides long-lasting COMT-inhibition due to the high binding affinity and a slow dissociation rate of the opicapone-COMT-complex. After 24 h, COMT activity is only reduced by approx.…”
Section: Introductionmentioning
confidence: 99%
“… 8 A recent meta-analysis concluded that opicapone is superior to both entacapone and tolcapone in terms of efficacy and safety. 6 …”
Section: Introductionmentioning
confidence: 99%